Mode of delivery and its associated obstetric and fetal outcome: a retrospective study - Mahyavanshi, Darshankumar K.; Patel, Mitali G.; Nayak, Sunil; Patel, Damini; Parmar, Asmi; Patel, Dhara (International Journal Of Community Medicine And Public Health, 2018)
Background: The number of maternal death has decreased by 43% from an estimated 532 000 in 1990 to 303 000 in 2015. The progress is notable, but the annual rate of decline is less than half of what is needed to achieve the Millennium Development Goal (MDG) target of reducing the maternal mortality ratio by 75% between 1990 and 2015, which would require an annual decline of 5.5%. Our aims of study to evaluate the mode of delivery and its obstetric and fetal outcomes and to find out the association between Mode of delivery with socio demographic and medical complication. Methods: Study design was a retrospective analytical record based study. In study setting, conducted in tertiary care hospital at GMERS Medical College and Civil hospital, Valsad, Gujarat. Detailed information is obtained from last 6 months review of data from obstetric and gynecology department. A data analysis of the outcome was carried out by using appropriate statistical test and MS excel. Results: out of total 692 mothers for maternal age majority of them from the age group of 21-25 ages followed by 26- 30 yrs of age which were 46.96% and 24.27% respectively. Out of the 644 babies majority of babies were born at term (43.43%) followed by very low birth weight (41.55%). Conclusions: No statistically proven association found between modes of delivery with mothers socio demographic characteristics and between mothers literacy status with weight of child and week of gestations.